Pengaruh Pengembangan Sumber Daya Manusia Terhadap Pelayanan Kesehatan Masyarakat Pada Puskesmas Atapange Kecamatan Majauleng - Yusran Yusran; Yuniarni Yuniarni (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to find out how well the development of Human Resources and employee work productivity and the influence of Human Resource development on employee work productivity at the Wajo District Samsat Office. The population in this study were 41 people, while the Taro Yamane Formula in Slovin was used to determine the number of samples, so that the sample obtained was 29 people. The data collection techniques were carried out through observation, documentation and distributing questionnaires.